2020
DOI: 10.3390/en13215818
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Working Machines Synergy in the Process of the Hybrid Electric Vehicle Acceleration

Abstract: There are many different mathematical models that can be used to describe relations between energy machines in the power-split hybrid drive system. Usually, they are created based on simulations or measurements in bench (laboratory) conditions. In that sense, however, these are the idealized conditions. It is not known how the internal combustion engine and electrical machines work in real road conditions, especially during acceleration. This motivated the authors to set the goal of solving this research probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Meanwhile, they have changed the equivalent factor value according to the current SOC state and its upper and lower limit [9]. The real vehicle test results have confirmed that the ECMS algorithm with known working conditions can achieve a better fuel-saving effect through the comparison between the influence of known driving conditions and unknown driving conditions on the ECMS algorithm [10].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, they have changed the equivalent factor value according to the current SOC state and its upper and lower limit [9]. The real vehicle test results have confirmed that the ECMS algorithm with known working conditions can achieve a better fuel-saving effect through the comparison between the influence of known driving conditions and unknown driving conditions on the ECMS algorithm [10].…”
Section: Introductionmentioning
confidence: 85%
“…Based on the equivalent voltage and current, the simplified ECMS optimization problem can be expressed as in equation ( 10). (10) In equation (10), denotes the equivalent power of ECMS, μ stands for the equivalent voltage related to the equivalent power corresponding to the unit current of the battery, and λ represents the equivalent factor of WL-ECMS.…”
Section: Energy Management Based On Wl-ecms (Ecms Based On the Willans Line Model)mentioning
confidence: 99%
“…Numerous studies [1][2][3][4][5][14][15][16][17][18]35,36] of hydrogen wear of the cylinder-piston group of internal combustion engines have shown the dominant role of both technological (internal) and operational (external hydrogen) in the wear of piston rings. The determination of the content of hydrogen in the parts was carried out by vacuum extraction.…”
Section: Hydrogen Wear Of Piston Rings Of Engine Cylinders and Ways T...mentioning
confidence: 99%
“…An augmented model of the plant is used to predict the plant responses. In recent works, predictive control is applied in driving systems [37][38][39], microgrids [40][41][42], HVAC systems [43,44], and other applications.…”
Section: Many Types Of Angular Position Sensors Were Developed For Inmentioning
confidence: 99%